Walk of shame - Brill, Steven; Marsden, James, 1973-; Banks, Elizabeth, 1974- (Universal Studios Home Entertainment, 2014)
After losing an audition for her dream job, an aspiring Los Angeles TV news anchor goes out for an uncharacteristic night of partying. She awakes in a stranger's bed to a phone message from her agent telling her the job is hers, if she can make it across town by 5 pm. Stranded in an unknown area without money, a phone, and a car, she embarks on a series of misadventures as she races to the most important job interview of her life.